Mathematical Modelling Of Thin Layer Drying Kinetics Of Paddy Straw Mushroom (Volvariella Volvacea) (International Journal of Food and Nutritional Sciences, 2022)
This study was conducted to investigate the drying kinetics of paddy straw mushroom (Volvariella volvacea). Mushrooms were dried using different drying methods and parameters were studied for preparation of dried mushroom. Mushrooms were dried in a tray dryer (50, 60 and 70°C), microwave convective dryer (0.72, 1.44 and 2.16 W/g power levels and constant air temperature of 50°C). The experimental drying data were fitted to different theoretical models to predict the drying kinetics. Results indicated that the Page model offered the best fit for experimental drying data for hot air drying and Wang and Singh model for microwave convective drying. The value of effective diffusivity in Microwave convective drying was more than that of hot air drying. The calculated activation energy (Ea) was 0.269W/g in Microwave convective drying and 44.97 kJ/mol in hot air convective drying.